Childhood maltreatment and personality disorders in adolescents and adults with psychotic or non-psychotic disorders - Wang, WenZheng; Cui, Yin; Hu, Qiang; Wei, YanYan; Xu, LiHua; Tang, XiaoChen; Hu, YeGang; Liu, HaiChun; Wang, ZiXuan; Chen, Tao; Wang, Ran; An, CuiXia; et al. (Frontiers in Psychiatry, 2024)
While the attention to personality disorders (PD) and childhood maltreatment (CM) has grown in recent years, there remains limited understanding of the prevalence and distinctions of PD and CM in clinical populations of Chinese adolescents in comparison to adults. A total of 1,417 participants were consecutively sampled from patients diagnosed with either psychotic or non-psychotic disorders in the psychiatric and psycho-counseling clinics at Shanghai Mental Health Center. The participants were categorized into two groups based on their age: adolescents (aged 15-21 years) and adults (aged 22-35 years). PDs were evaluated using a self-reported personality diagnostic questionnaire and a structured clinical interview, while CMs were assessed using the Chinese version of the Child Trauma Questionnaire Short Form. When comparing selfreported PD traits and CM between adolescents and adults, differences emerge. Adolescents, particularly in the psychotic disorder group, exhibit more pronounced schizotypal PD traits (p=0.029), and this pattern extends to non-psychotic disorders (p<0.001). Adolescents in the nonpsychotic disorder group also report higher levels of emotional abuse (p=0.014), with a notable trend in physical abuse experiences compared to adults (p=0.057). Furthermore, the most prevalent PDs in the clinical sample are avoidant, borderline, and obsessive-compulsive PDs. Among patients with psychotic disorders, adolescents exhibit higher rates of schizoid, schizotypal, and obsessive-compulsive PDs compared to adults. Logistic regression analyses highlight distinct predictors for psychotic and non-psychotic disorders in adolescents and adults. The findings emphasize distinct differences in PDs and CMs between adolescent and adult groups, shedding light on their potential roles in psychotic and non-psychotic disorders.